Transferring between sports: the case of Icelandic youth sport - Donoghue, P. O.; Maute, M. M.; Jóhannsson, K. V.; Þorgeirsson, S.; Kristjánsdóttir, H.; Saavedra, J. M.; Oddsson, H. R (International Journal of Computer Science in Sport, 2025)
The purpose of the current investigation was to describe transfers between Icelandic youth sports and to compare drop-out from sport between those doing single sports, those doing multiple sports without transferring, and those transferring between sports. 11,382,013 youth sport invitation records sent to over 40,925 young athletes over a two-year period were analysed. Drop-out and transfers between sports were determined using the first and last attendances of players in different sports. There was net transfer from gymnastics and swimming to other sports, as well as a net transfer from soccer to handball and basketball. Girls had a net transfer from athletics and individual games to team games while boys had a net transfer from team games to athletics and individual games. The percentage of players dropping out of sport was 35.5% for those doing a single sport, 6.5% for players doing multiple sports without transferring, and 18.1% for players doing multiple sports over the two-year period and transferring between sports. These differences between drop-out rates were significant for both girls (p < 0.001) and boys (p < 0.001). Young people should be encouraged to participate in multiple sports to avoid dropping out of sport before they become adults.